PENERAPAN METODE ALGORITMA GENETIKA UNTUK PERMASALAHAN PENJADWALAN PERAWAT - Nadiya Hijriana (Universitas Lambung Mangkurat, 2015)
Nurse have an important role that influencing performance and quality of service user at hospital. Therefore, hospital management needed to create a good schedule so that user (patient) in the hospital can get good service also. At this research, what studied is how to develop a computerized nurse-scheduling model that implemented a genetic algorithm method. Making model is accounts to some objectives and policies at Islamic Hospital of Banjarmasin.By using software of Delphi XE2 to developing model, then some experiments used to test the model and giving result that a computerized nurse scheduling with a genetic algorithm method is more effiecient and effectivethan manual made-schedules. Keywords: Nurse scheduling, Genetic algorithm